Project Development and Participation in Competitions as Strategies for the Development of Employability Skills Required by Knowledge Oriented Sectors - Margarita Tecpoyotl Torres; Jonathan Villanueva-Tavira; Andrea Magadán-Salazar; Karla G. Cedano-Villavicencio (CLEI Electronic Journal)
This paper shows the results obtained by applying the Methodology for Development of Potentially Innovative Technological Projects, focused on employability based on the skills and competencies developed. Among them are communication, the management project, technical knowledge, critical thinking, entrepreneurship, innovation and leadership. One of the first stages of the methodology involves the motivation and commitment of the students with the projects to be developed, while in the last stages there is the participation in competitions, which are a way of making visible the projects carried out, as well as the potential and rigorous training of the participants, which is not limited to techno-scientific skills and knowledge, but also involves complementary skills and competencies valued by employers in companies corresponding to the knowledge-oriented sectors. The dissemination stage is another of the final stages of the methodology, which has contributed to the visibility of results at regional, national and international levels, showing that the globalized scope is a valuable tool for the insertion of graduates in the productive sector.